2013
DOI: 10.1007/s12010-013-0593-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Assisted Plasma Deposition of Hydrophobic Polycations Makes Surfaces Highly Antimicrobial

Abstract: The currently used multistep chemical synthesis for making surfaces antimicrobial by attaching to them hydrophobic polycations is replaced herein by an aerosol-assisted plasma deposition procedure. To this end, N,N-hexyl,methyl-PEI (HMPEI) is directly plasma-coated onto a glass surface. The resultant immobilized HMPEI coating has been thoroughly characterized and shown to be robust, bactericidal against Escherichia coli, and virucidal against human influenza virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In another approach for coating the polycations, a study by Liu et al demonstrated use of N , N -hexyl,methyl-polyethylenimine with an aerosol-assisted plasma deposition technique on glass surfaces. 89 This allows for the covalent immobilization of N , N -hexyl,methyl-polyethylenimine through a one-step method and has been shown to be thermally stable (up to 150 °C) and durable upon exposure to vigorous washes and exposure to detergents. This study demonstrated a greater than 4-log reduction in the influenza H1N1 virus for N , N -hexyl,methyl-polyethylenimine-treated surfaces.…”
Section: Polymeric and Organic Antiviral Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another approach for coating the polycations, a study by Liu et al demonstrated use of N , N -hexyl,methyl-polyethylenimine with an aerosol-assisted plasma deposition technique on glass surfaces. 89 This allows for the covalent immobilization of N , N -hexyl,methyl-polyethylenimine through a one-step method and has been shown to be thermally stable (up to 150 °C) and durable upon exposure to vigorous washes and exposure to detergents. This study demonstrated a greater than 4-log reduction in the influenza H1N1 virus for N , N -hexyl,methyl-polyethylenimine-treated surfaces.…”
Section: Polymeric and Organic Antiviral Coatingsmentioning
confidence: 99%
“…This study demonstrated a greater than 4-log reduction in the influenza H1N1 virus for N , N -hexyl,methyl-polyethylenimine-treated surfaces. 89 …”
Section: Polymeric and Organic Antiviral Coatingsmentioning
confidence: 99%
“…In one example study, Liu et al covalently immobilized N, N-hexyl, methyl-PEI (HMPEI) using an atmospheric-pressure plasma liquid deposition method. They showed that HMPEI-coated glass slides generated by plasma exposure reduced the viral titer of human influenza A (H1N1) virus compared to control, as well as the bacterial titer of waterborne E. coli [93].…”
Section: Cationic Polymersmentioning
confidence: 99%
“…[ 266 ] N , N ‐hexyl,methyl‐PEI (HMPEI) has also been investigated as a candidate for coating deposited via an aerosol‐assisted plasma method and exhibited virucidal properties. [ 136 ] However, the cytotoxicity of DMPEI and its correlation with antiviral activity should be explored for clinical applications. [ 133 ] Hydrophobic and cationic polyacrylamides and acrylate‐based polymers exhibit virucidal activity against enveloped [ 138 ] and nonenveloped viruses.…”
Section: Polymers Against Virusesmentioning
confidence: 99%
“…The antiviral polymers mentioned above have been commonly studied for their therapeutic applications. However, some of these polymers with extracellular and direct antiviral activity have also been successfully applied as coatings [ 136 ] and in food. [ 270,271 ] Thus, the redirection of these materials for other purposes, such as for “self‐sanitizing surfaces,” is plausible and should be further explored.…”
Section: Polymers Against Virusesmentioning
confidence: 99%